2010
DOI: 10.1021/ja102775u
|View full text |Cite
|
Sign up to set email alerts
|

Magic Angle Spinning NMR Analysis of β2-Microglobulin Amyloid Fibrils in Two Distinct Morphologies

Abstract: Abstractβ 2 -Microglobulin (β 2 m) is the major structural component of amyloid fibrils deposited in a condition known as dialysis-related amyloidosis. Despite numerous studies that have elucidated important aspects of the fibril formation process in vitro, and a magic angle spinning (MAS) NMR study of the fibrils formed by a small peptide fragment, structural details of β 2 m fibrils formed by the full-length 99-residue protein are largely unknown. Here, we present a site-specific MAS NMR analysis of fibrils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
124
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(128 citation statements)
references
References 90 publications
4
124
0
Order By: Relevance
“…Here, it is worth noting that recent studies have suggested similar features in other proteins. For ␤2m and prion proteins, domain-swapped dimers have been observed (19,20), but for both proteins ssNMR and ESR studies on fibrils have indicated an IP sheet structure and a loss of the native conformation (51,(62)(63)(64)(65). Thus, at least in a number of cases, similar observations have been made, when mature fibrils were studied directly.…”
Section: Discussionmentioning
confidence: 77%
“…Here, it is worth noting that recent studies have suggested similar features in other proteins. For ␤2m and prion proteins, domain-swapped dimers have been observed (19,20), but for both proteins ssNMR and ESR studies on fibrils have indicated an IP sheet structure and a loss of the native conformation (51,(62)(63)(64)(65). Thus, at least in a number of cases, similar observations have been made, when mature fibrils were studied directly.…”
Section: Discussionmentioning
confidence: 77%
“…5). Subsequent isomerization of the prolyl bond during fibril maturation would then exclusively afford the trans isomer observed by solid-state NMR (14,15). Furthermore, growth kinetics for [F 2 Pro32]β2m amyloids shows that the activation energy for isomerization of amide32 also influences fibril assembly.…”
Section: Discussionmentioning
confidence: 98%
“…Several lines of evidence, including detailed folding studies and mutagenesis experiments on β2m, have suggested that cis-to-trans isomerization of Pro32 serves as a trigger to misfolding and subsequent aggregation (6,13). In β2m amyloids, this residue adopts a trans conformation (14,15), and additives that increase the equilibrium concentration of β2m conformers containing trans-Pro32 have been shown to promote amyloid formation (11). A transproline amide is also observed in the X-ray structure of the hexameric species that is formed upon treatment of the H13F variant with Cu 2+ ions (7).…”
mentioning
confidence: 99%
“…Relationship between Fibril Polymorphism and Hydrophobic Interactions-As for the polymorphic features of ␤2-m fibrils reported so far, several distinct forms are known to be produced, depending on experimental conditions such as the concentration of salt (15,33,34,47), pH (30,33), and the reduction of disulfide bonds (48). Although the polymorphic structure caused by the pH and NaCl concentration suggests a role for electrostatic interactions in determining fibril structure, it has not been clarified what characteristics of side chain interactions influence the resulting fibril structure most critically.…”
Section: Formation Of Amyloid Fibrils In Tfe-mentioning
confidence: 98%
“…Although some of this morphological diversity may emerge simply from differences in the hierarchical assembly of a single type of protofilament (9), recent research has revealed microscopic structural diversity underlying each protofilament, such as the amount of cross-␤ core, parallel/antiparallel alignment of ␤-strands, protofilament core topology, and, additionally, more minute structural variety observed at an amino acid level, as detected by using hydrogen/deuterium exchange NMR spectroscopy (10,11), solid-state NMR spectroscopy (12)(13)(14)(15), cryo-EM (16), x-ray crystallography with microcrystals (17,18), and Fourier transform infrared spectroscopy (19,20). For a comprehensive understanding and for regulation of the structure and function of each type of amyloid fibril, elucidation of the interactions inside the polypeptide chains constituting the fibrils is essential.…”
mentioning
confidence: 99%